2020
DOI: 10.18203/2349-3291.ijcp20204043
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in relation to severity of retinopathy of prematurity in preterm babies born in tertiary care centre in South India

Abstract: Background: Retinopathy of prematurity (ROP) is a vaso proliferative disorder of retina among preterm infants. Significant cause of blindness in children with increased survival of premature infants with improved neonatal care. Potential risk factors for development of ROP include low gestational age, low birth weight, bronchopulmonary dysplasia, sepsis, acidosis, oxygen therapy. Anemia as a cause for retinopathy of prematurity has been postulated but there are very few studies addressed the effect of anemia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…18,19 Likewise, anemia and blood transfusion has been reported as an independent risk factor of ROP in premature infants. 20 On the contrary, in the literature, the effect of maternal PIH on the occurrence of ROP is not conclusive and requires further analysis. 21 Overall, based on the present findings, it can be inferred that multiple neonatal risk factors are associated with the development of ROP and effort should be made to control these factors to reduce the risk of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Likewise, anemia and blood transfusion has been reported as an independent risk factor of ROP in premature infants. 20 On the contrary, in the literature, the effect of maternal PIH on the occurrence of ROP is not conclusive and requires further analysis. 21 Overall, based on the present findings, it can be inferred that multiple neonatal risk factors are associated with the development of ROP and effort should be made to control these factors to reduce the risk of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, anemia, thrombocytopenia, blood transfusions, IVH and sepsis were independent risk factors of ROP, especially with progression to severe ROP. This is similar to studies by Pai et al .,[ 23 ] Lim et al .,[ 24 ] Pascal et al .,[ 25 ] and Chang. [ 26 ] All these factors add to the oxidative stress on the immature retina, thereby up regulating VEGF levels, which eventually leads to neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the etiology of ROP, the major risk factors for the disorder are low birth weight (BW), low gestational age (GA), and oxygen therapy [ 4 - 6 ]. In addition, several studies have suggested that blood transfusions, mechanical ventilation, and sepsis are the other factors that contribute to an increased incidence of ROP in premature infants [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%